UNDERSTANDING THE IMPACT OF SKILL-BIASED TECHNOLOGICAL CHANGE: AN EXPLORATORY STUDY OF INDIAN ECONOMY - Manju Singh, Minali Banerjee, Bhaskar Arora, Monika Mathur, Saurabh Sharma (International Journal of Advanced Science and Technology, 2020)
The sculpture of the world is continuously changing shape and every change boasts some opportunities and challenges. Demand for new and upgraded Technology is the need of the hour. Perhaps, this piece of research focuses on skill augmenting capabilities of unskilled labours through Technological advancement which is considered to be a trickle-down effect of skill biased technological change. The article concludes from its supporting theories that long run impact of technological advancement is skill augmentation by converting unskilled labour to skill labour.